2015
DOI: 10.1016/j.bpj.2014.11.3487
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Entropic Collapse of Coarse-Grained Chromosomes

Abstract: Depletion forces play a role in the compaction and decompaction of chromosomal material in simple cells, but it has remained debatable whether they are sufficient to account for chromosomal collapse. We present coarse-grained molecular dynamics simulations, which reveal that depletion-induced attraction is sufficient to cause the collapse of a flexible chain of large structural monomers immersed in a bath of smaller depletants. These simulations use an explicit coarse-grained computational model that treats bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 82 publications
5
70
0
Order By: Relevance
“…For instance, a computational approach has shown the interplay between crowder size and density in collapsing a flexible chain in a cylindrical space 16 . The compaction in this case appears to be continuous, similarly to a corresponding unconfined case 17,18 . More recently, the interdependence of chain length and compaction has been discussed 20 .…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…For instance, a computational approach has shown the interplay between crowder size and density in collapsing a flexible chain in a cylindrical space 16 . The compaction in this case appears to be continuous, similarly to a corresponding unconfined case 17,18 . More recently, the interdependence of chain length and compaction has been discussed 20 .…”
Section: Introductionmentioning
confidence: 86%
“…Thanks to recent efforts, several key features of chain collapse by molecular crowding have begun to emerge 8,[16][17][18][19][20] . For instance, a computational approach has shown the interplay between crowder size and density in collapsing a flexible chain in a cylindrical space 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macromolecular crowders are unlikely to be the only determinants of chromosome compaction, as Shendruk et al (2015) concluded from observing a continuous rather than first-order transition as in experiments (Pelletier et al 2012). One such factor, i.e., DNA binding proteins (DBPs), has been studied by Brackley et al (2013b).…”
Section: Computational Models Of the Genetic Materialsmentioning
confidence: 90%
“…Accordingly, crowders have often been modeled as inert hard spheres to capture the effect of volume occlusion. This approximation has led to the prediction that inert crowders promote folding and chemical reactions (Muramatsu and Minton 1988;Zhou et al 2008), as well as to observing the reversible transition from a swollen to a compact chromosome (Shendruk et al 2015) and the assembly of nuclear bodies in computer simulations (Cho and Kim 2012b;Kim and Szleifer 2014).…”
Section: Introductionmentioning
confidence: 99%